Elaborate doorframe/architrave of the Gateway - Temples of India Project Team (Jio Institute, 2024)
A visitor may enter through the elaborate doorframe/architrave of the gateway (pratoli). It has intricate designs on the shakkhas (vertical bands), sculpture at the bottom and an image of a seated Lakuslisa at the centre of the latatabimba (lintel). The Lakuslisa figure is holding a club in hand. The doorframe has depictions of Shaiva dvarapalas (door guardians) on both sides.